Design and Fabrication of Animal Waste Cleaning Machine - Parajuli, Laxmi; K.C., Samundra; Paudel, Saroj; Khatri, Subash; Neupane, Surakshya (Kathmandu University Journal of Science, Engineering and Technology, 2021)
Cleaning is an essential and unavoidable part of life, and cleaning animal shed waste is a time-consuming activity that may be better spent on something more productive. During discussions with dairy farmers in Nepal, it became evident that animal waste collecting equipment was required. One of the primary reasons for this requirement is labor scarcity, which is caused by employees’ dislike of picking and collecting animal dung manually. Animal waste cleaning machine provides a strategy for collecting animal dung and cleaning the space without putting people in close contact with the dung. A chain drive mechanism is used in this machine. The dung is collected with the help of picker/rubber pads that are welded to the chain, then dropped into the collector, and the process is repeated. The chain is coupled to a 12V battery-powered dc motor. The machine is cost-effective and saves time by reducing human labor. It may also be utilized as a stand-alone device in remote areas.